In the Suburbs of History : Modernist Visions of the Urban Periphery - Logan, Steven, 1974- (Book collections on Project MUSE., 2021)
"In the 1960s, socialist and capitalist urban planners, architects, and city officials chose the urban periphery as the site to test out new ideas in modernist architecture and planning: the outskirts of Prague and a bedroom suburb of Toronto would be the sites for experimental urban development. In the Suburbs of History overcomes the divisions between East and West to reassemble the shared histories of modern architecture and urbanism as it shaped and re-shaped the periphery. Drawing on archives, interviews, architectural journals, and site visits to the peripheries of Prague and Toronto, Steven Logan reveals the intertwined histories of capitalist and socialist urban planning. From socialist utopias to the capitalist visions of the edge city, the history of the suburbs is not simply a history of competing urban forms; rather, it is a history of alternatives that advocated collective solutions over the dominant model of single-family home ownership and car-dominated spaces."--